Réponses

2014-01-22T15:43:48+01:00
Exercice 15
a.
A = 5x + 2x + 10x
B = 27x² - 27x + 27
C = 9x(x-3) + 9x(10+2x)
D = (2x+1)(8+x) - (3x-1)(2x+1)

b.
A = 5x + 2x + 10x
A = x(5 + 2 + 10)
A = 17x

B = 27x² - 27x + 27
B = 27(x² - x + 1)

C = 9x(x-3) + 9x(10+2x)
C = 9x[(x-3) + (10+2x)]
C = 9x(3x+7)

D = (2x+1)(8+x) - (3x-1)(2x+1)
D = (2x+1)[(8+x) - (3x-1)]
D = (2x+1)(8+x-3x+1)
D = (2x+1)(9-2x)

Exercice 16
a.
E = 10x² - 5x + 15
E = 5*2x² - 5x + 5*3

F = 4x² + 7x
F = 4x*x + 7x (* signifie multiplié par)

G = 9x²(x+1) + 6x(5+x)
G = 3x*3x(x+1)+ 3x*2(5+x)

H = (11x-3)² + (11x-3)(5+9x)
H = (11x-3)(11x-3) + (11x-3)(5+9x)

b.
E = 10x² - 5x + 15
E = 5*2x² - 5x + 5*3
E = 5(2x²-x+3)

F = 4x² + 7x
F = 4x*x + 7x
F = x(4x+7)

G = 9x²(x+1) + 6x(5+x)
G = 3x*3x(x+1) + 2*3x(5+x)
G = 3x[3x(x+1) + 2(5+x)]
G = 3x(3x²+3x + 10+2x)
G = 3x(3x²+5x+10)

H = (11x-3)² + (11x-3)(5+9x)
H = (11x-3)(11x-3) + (11x-3)(5+9x)
H = (11x-3)(11x-3+5+9x)
H = (11x-3)(20x+2)
H = 2(10x+1)(11x-3)